Drying Kinetics of Banana Chips: A Modeling Approach - Hermanuadi, Didik; Iswahyono, Iswahyono; Kurniawati, Elly; Djamila, Siti; Bahariawan, Amal (The University of Lampung, 2024)
The primary goal of this research is to identify and evaluate the most suitable thin-layer drying model to effectively interpret the drying characteristics of banana chips and determine moisture diffusivity at different drying temperatures. The study utilized physiologically mature “kapok” bananas from the local market in Jember Regency. A flash dryer with a 4000-watt electric heating system was used, equipped with a blower for air circulation, an exhaust fan to expel water vapor. The bananas were processed into chips with a thickness of 1 mm. A total of 2000 g of banana chips were dried at constant temperature according to treatment conditions (air velocity 3.2 m/s, drying at temperatures of 60, 70, and 80°C). The study found that higher drying temperatures (80°C) achieved the highest initial drying rate (35.9% in 30 min) compared to 60°C (28.0%) and 70°C (22.0%). However, the drying rate gradually decreased at all temperatures. The drying kinetics of banana chips at 60, 70, and 80°C aligned well with the modified Midilli model. Effective moisture diffusivity values for banana chips at 60, 70, and 80°C were 4.947E-9 m²/s, 5.165(10–9) m²/s, and 5.756(10–9) m²/s, respectively, indicating that drying at 80°C was the most effective. The effective moisture diffusivity value showed a strong correlation with air velocity, drying temperature, material thickness, RH, and specific material attributes. Keywords: Banana, Diffusivity, Drying, Thin layer drying, Modified Midilli Model.